PERAN ZIS DALAM MENINGKATKAN KESEJAHTERAAN PEREMPUAN: STUDI PADA PROGRAM BUNDA MANDIRI SEJAHTERA LAZNAS YATIM MANDIRI - Tanjung, Nabila Azzahra; Rohim, Ade Nur (Ekonomi Islam, 2024)
Zakat, infaq, and sadaqa (ZIS) play a role in alleviating poverty. However, Indonesia is still faced with the problem of poverty among women. This research aims to find out and analyze the implementation of ZIS distribution through the Bunda Mandiri Sejahtera (BISA) program and its implications for the welfare of Mustahiq. The method used in this research is descriptive statistics with a case study approach using the CIBEST model. The research findings show that the distribution of ZIS through the BISA program provides studies, grants, and business capital. The result also indicates that the BISA program has implications for increasing welfare where more than half of Mustahiq in quadrant 1. Keywords: ZIS, Women Mustahiq, Welfare, CIBEST